Analisis Peran Laba Pembiayaan (Akad Mudharabah dan Musyarakah) Terhadap Profitabilitas Bank Syariah Indonesia: Studi Banding dengan Profitabilitas Bank Konvensional KBMI III Periode 2021-2023 - Hartomo, Prasetiyo (Journal of Economics and Management, 2024)
This research aims to analyze the effect of mudharabah and musyarakah financing profits on BSI Bank profitability as well as a comparative study of the profitability of KBMI III Conventional Banks for the 2021-2023 period. The sample in this study used a proportionate stratified random sampling technique which took profit data on mudharabah and musyarakah financing at Bank Syariah Indonesia and profitability data (ROA) at Bank Syariah Indonesia, Bank BTN, Bank Permata and Bank CIMB Niaga for the 2021-2023 period. The analytical tool used is multiple linear regression analysis using the SPSS V21 application. The research results showed that the mudharabah financing profit variable had a negative and significant effect on profitability and the musyarakah financing profit variable had a positive and significant effect on profitability, while the test results of mudharabah and musyarakah financing profits together had a positive and significant effect on profitability. The results of different test research show that in general the ROA of Bank BSI is better than that of conventional Bank KBMI III.